2009
DOI: 10.1017/s0033291708005102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of induced anger in patients with antisocial personality disorder

Abstract: ASPD patients did not display a deviant self-reported anger but physiological hyporesponsivity and cognitive hyper-responsivity. This ASPD anger response might reflect a controlled predatory-like fight preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 36 publications
(38 reference statements)
4
47
0
Order By: Relevance
“…Furthermore, results show faster response time in the post Anger-Single Target Implicit Association Test 42 , indicating a stronger ‘self’-‘anger’ concept association after provocation, but these results are non-significant and there is no differences in implicit anger between VOF and NOC (see Table 2). …”
Section: Methodsmentioning
confidence: 90%
“…Furthermore, results show faster response time in the post Anger-Single Target Implicit Association Test 42 , indicating a stronger ‘self’-‘anger’ concept association after provocation, but these results are non-significant and there is no differences in implicit anger between VOF and NOC (see Table 2). …”
Section: Methodsmentioning
confidence: 90%
“…Notably, all three groups showed comparable self-reported emotional responses, similar to results from Habel et al (2002) using a mood induction paradigm. Applying an anger induction to a sample of offenders with antisocial personality disorder, Lobbestael et al (2009) reported cardiovascular hyporeactivity compared to controls but again no differences in self-reported anger levels. Testing non-psychopathic offender groups with and without antisocial personality disorder, Wahlund et al (2010) also observed lower skin conductance responses (SCRs) but also reduced self-reported emotional responses to negative pictures.…”
Section: Introductionmentioning
confidence: 87%
“…In a similar vein, Blackburn and Lee-Evans (2011) found that psychopathic participants anticipated that they would respond with greater anger than non-psychopaths to a variety of anger-inducing scenarios. Lobbestael et al (2009) performed an anger induction task in individuals with Antisocial Personality Disorder (who varied in psychopathic traits), Borderline Personality Disorder and controls. The induction task entailed recalling a situation in which subjects had experienced a conflict with another person and had felt very angry, after which subjects spent several minutes recalling the details of the event.…”
Section: Psychopathy and Fear Respondingmentioning
confidence: 99%